Quantitative synthesis of bis(cyclic carbonate)s by iron catalyst for non-isocyanate polyurethane synthesis. Issue 1 (25th September 2014) - Sheng, Xingfeng; Ren, Guanjie; Qin, Yusheng; Chen, Xuesi; Wang, Xianhong; Wang, Fosong
Abstract : Polyurethanes were prepared from the polyaddition of diamines and bis(cyclic carbonate)s which were obtained via the complete carbonation of diepoxides. Abstract : Bis(cyclic carbonate)s were quantitatively prepared with high efficiency via the coupling reaction of carbon dioxide (CO2 ) with diglycidyl ethers by a [Fe(BPMCDAC)]/TBAB catalytic system, where glycol diglycidyl ether (1a ) could be completely converted to the corresponding bis(cyclic carbonate) (2a ) with a turnover number of 1000 at 100 °C and 3 MPa in 4 h. The obtained bis(cyclic carbonate) (2a ) could be used to prepare hydroxyl-functional polyurethanes via reaction with diamines, which may be one alternative for obtaining conventional polyurethanes without the use of toxic phosgene or isocyanates. The number-average molecular weights of the obtained non-isocyanate polyurethanes (NIPUs) were up to 25.4–30.2 kg mol −1, and the polydispersity indexes (PDIs) were relatively narrow between 1.18 and 1.22. A typical NIPU showed a glass transition temperature of 9 °C and an initial degradation temperature ( T d 5% ) of 206 °C.